Climber, Camper, and Quitter: How Solve Ethnomathematics Based Mathematics Problem - Plavantiano Labiodonta Aviko Veola; Nuqthy Faiziyah (STAI Hubbulwathan Duri, 2023)
Problem-solving ability is the capacity to think critically and determine solutions for specific problems. This study aims to assess the problem-solving skills of students in tackling High Order Thinking Skills (HOTS) problems, focusing on students with different Adversity Quotient (AQ) types: quitter, camper, and climber. A qualitative descriptive method was employed to evaluate the students' abilities in solving Systems of Linear Equations in Two Variables (SPLDV) problems. The subjects of this study were students categorized into quitter, camper, and climber AQ types. Data collection methods included: 1) written tests to evaluate problem-solving skills, 2) questionnaires to assess AQ levels, and 3) interviews to clarify students' confidence levels. The results indicated that students with the quitter AQ type could only complete one stage of problem-solving. Those with the camper AQ type managed to complete two stages, while students with the climber AQ type were able to successfully complete all four stages of problem-solving, despite encountering minor errors in the process.